2020
DOI: 10.1155/2020/3073906
|View full text |Cite
|
Sign up to set email alerts
|

Mycochemical Screening and Analysis, Antioxidant Activity, and Biochemical Composition of Fermentation Strain Snef1216 (Penicillium chrysogenum)

Abstract: Antioxidants are the radical scavengers that inhibit peroxidation and other free-radical processes, which in return safeguard different organisms from various diseases attributed to radical reactions. Synthetic antioxidants inhibit free radicals, but they also have harmful side effects. However, mycochemicals of natural fungal origin are safe and best substitutes for harmful synthetic chemical antioxidants. The prime objectives of the study include appropriate qualitative and quantitative mycochemical screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…The best antiradical activity observed with the P. oxalicum extract from the soil, would be due to the phenolic compounds [48]. Indeed, similar results have been reported by other authors who have shown that there is a relationship between the content of phenolic compounds and the antiradical activity of fungi extracts [49,50].…”
Section: Assessment Of Antioxidant Activitysupporting
confidence: 81%
“…The best antiradical activity observed with the P. oxalicum extract from the soil, would be due to the phenolic compounds [48]. Indeed, similar results have been reported by other authors who have shown that there is a relationship between the content of phenolic compounds and the antiradical activity of fungi extracts [49,50].…”
Section: Assessment Of Antioxidant Activitysupporting
confidence: 81%
“…Antioxidants play an important role in cell protection by blocking free radicals at their active site and trapping free radicals that cause degenerative processes [ 54 , 55 ]. Previous research has demonstrated that Penicillium chrysogenum has a strong antioxidant capacity [ 11 , 42 ]. The antioxidant activity of P. chrysogenum MZ945518 has an IC 50 of 542.5 µg/mL in the DPPH test.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous species within the genus, some of which are commercially important in nutrition, biomedical, and pharmaceutical production [ 10 ]. Due to the abundance of bioactive components, such as flavonoids, alkaloids, minerals, proteins, phenols, tannins, vitamins, and antioxidant characteristics, these organisms were able to biosynthesize a diverse array of primary and secondary metabolites [ 11 ]. Anticancer, antibacterial, and antioxidant effects are demonstrated by many species of this genus [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The plant powder, as well as ethanol, ethyl acetate, and petroleum ether extracts, was screened for their phytochemical constituents (alkaloids, saponins, cardiac glycosides, flavonoids, phenols, triterpenoids, and tannins). The phytoconstituents were identified by characteristic colour change using standard procedures by Sikandar et al [ 16 ], performing each experiment in triplicate.…”
Section: Methodsmentioning
confidence: 99%